Dampak Penerapan Pembelajaran Problem Based Learning bagi Siswa Kelas XIII IPS pada Mata Pelajaran Sosiologi di SMA Negeri 26 Tangerang - Sopian, Ahmad; Widiansyah, Subhan (TSAQOFAH, 2022)
This study aims to determine the impact of the application of problem-based learning for students in sociology class XIII social studies at SMA N 26 Tangerang Regency. The method used in this research is descriptive qualitative, to collect data the researcher uses question and answer media with sociology teachers (interviews) and observations, which are carried out to teachers and some students directly, in the process of interviewing research informants using unstructured interviews which questions can develop during the interview so that it becomes more flexible, and also explore several reference sources that support research by browsing relevant journals with the Based Learning (PBL) learning method. The results of this study describe that by using the problem-based learning method, students can be more enthusiastic and enthusiastic in learning and also discuss and present the problems studied in groups.